Re-scoping ultradian rhythms in the context of metabolism - van der Veen, Daan R.; Gerkema, Menno P. (Frontiers in Physiology, 2024)
Rapid, ultradian biological rhythms are only partly comparable to circadian (24-h) rhythms. Often, the ensuing expectations from this comparison are that 1) ultradian rhythms should be driven by discrete oscillators, 2) they are biochemically buffered, and 3) they must be functionally linked to extrinsic events and cycles. These three expectations are not always met, but perhaps there is an adaptive benefit to ultradian rhythms not meeting these expectations, which sets them functionally apart from circadian rhythms. In view of the extensive descriptions of the manifold types of ultradian rhythms across all biological levels (e.g., see papers in this research topic), it seems important to ask whether we should actively create a new set of definitions and expectations. To make a start, we here lay out some important questions we need to ask about ultradian rhythms. We then illustrate how these questions highlight one key area of exploration: the linked expression of ultradian rhythms in metabolism and behaviour and the role this plays in addressing a negative energy balance.